Sosialisasi prosedur pencairan dan pemberian pembiayaan pada anggota di KSPPS Fathul Hidayah As Salam - Kusmayasari, Dewi; Rahmaniayah, Fatichatur; Darmayanti, Novi; Ariyanti, Desy Fajar; Suhartono, Muhammad Yoyok (Nur Science Institute, 2025)
This community service activity involves the socialization of the disbursement and financing procedures for customers at KSPPS Fathul Hidayah As Salam. Initial observations revealed a gap in customer understanding of the flow and requirements of Sharia financing, which could hinder service efficiency and satisfaction. The main objective of this activity is to bridge the information gap and enhance customer literacy in Sharia-compliant financing. The method employed is a participatory and educational approach through comprehensive socialization at the KSPPS office during February 2025, targeting existing and new customers. The stages include preparing easy-to-understand materials, implementing interactive socialization with question-and-answer sessions, and evaluating understanding. The results showed significant obstacles in customer understanding regarding the process flow, technical terms, document requirements, and disbursement time expectations. A lack of customer initiative in seeking information was also identified. This gap could cause delays, incomplete files, and misconceptions. This socialization emphasizes the importance of adaptive and sustainable education strategies to improve customer understanding, support KSPPS efficiency, and align with the OJK’s mandate in consumer protection and sharia financial inclusion.